Comparing the molecular evolution and recombination patterns of predominant PRRSV-2 lineages co-circulating in China - Zhang, Riteng; Li, Hui; Xie, Honglin; Hou, Xiaolan; Zhou, Lixuan; Cao, Aiqiao; Zeshan, Basit; Zhou, Yefei; Wang, Xinglong (Frontiers in Microbiology, 2024)
Porcine reproductive and respiratory syndrome virus (PRRSV) poses widespread epidemics in swine herds, yet the drivers underlying lineage replacements /fitness dynamics remain unclear. To delineate the evolutionary trajectories of PRRSV-2 lineages prevalent in China, we performed a comprehensive longitudinal phylodynamic analysis of 822 viral sequences spanning 1991 to 2022. The objectives encompassed evaluating lineage dynamics, genetic diversity, recombination patterns and glycosylation profiles. A significant shift in the dominance of PRRSV-2 sub-lineages has been observed over the past three decades, transitioning from sub-lineage 8.7 to sub-lineage 1.8, followed by extensive diversification. The analysis revealed discordant recombination patterns between the two dominant viral sub-lineages 1.8 and 8.7, underscoring that modular genetic exchanges contribute significantly to their evolutionary shaping. Additionally, a strong association was found between recombination breakpoint locations and transcriptional regulatory sequences (TRSs).Glycosylation patterns also demonstrated considerable variability across sub-lineages and temporally, providing evidence for immune-driven viral evolution. Furthermore, we quantified different evolutionary rates across sub-lineages, with sub-lineage 1.8 uniquely displaying the highest nucleotide substitution rates. Taken together, these findings provide refined insight into the evolutionary mechanisms underpinning cyclic shifts in dominance among regionally circulating PRRSV sub-lineages.